2011
DOI: 10.1007/s10495-011-0640-y
|View full text |Cite
|
Sign up to set email alerts
|

Terfenadine induces apoptosis and autophagy in melanoma cells through ROS-dependent and -independent mechanisms

Abstract: Previously we found that terfenadine, an H1 histamine receptor antagonist, acts as a potent apoptosis inducer in melanoma cells through modulation of Ca2+ homeostasis. In this report, focusing our attention on the apoptotic mechanisms activated by terfenadine, we show that this drug can potentially activate distinct intrinsic signaling pathways depending on culture conditions. Serum-deprived conditions enhance the cytotoxic effect of terfenadine and caspase-4 and -2 are activated upstream of caspase-9. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 35 publications
5
51
1
2
Order By: Relevance
“…Antagonists of H1 receptor and activators of AMPK can induce autophagy (Nicolau-Galmes et al, 2011;Alers et al, 2012), thereby making olanzapine a promising target for glioma treatment. Evidences in recent years indicate that autophagy played a dual role in cancer cells depending on cell type, context or stage of tumor development (Mathew et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Antagonists of H1 receptor and activators of AMPK can induce autophagy (Nicolau-Galmes et al, 2011;Alers et al, 2012), thereby making olanzapine a promising target for glioma treatment. Evidences in recent years indicate that autophagy played a dual role in cancer cells depending on cell type, context or stage of tumor development (Mathew et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, Tomasini et al demonstrated in 2005 that TP53INP1 gene is a transcriptional target of p73, and that in turn, TP53INP1 modulates p73-induced cell cycle arrest and apoptosis by modulating p73 transcriptional activity, independently of p53. Several authors showed that p73 was induced in response to oxidative stress and was implicated in oxidative cellular response [50,51]. TP53INP1 could regulate redox status by activating p73 and thus transcription of target genes implicated against oxidative stress.…”
Section: Hypotheses On Tp53inp1 Antioxidant Functionmentioning
confidence: 99%
“…Besides blocking the H1 receptor, Terfenadine may interfere with degranulation of mast cells and thus decrease histamine release [5]. Terfenadine and related substances may further trigger apoptosis [11][12][13][14][15][16][17][18] and may thus be effective against malignancy [12-15, 17, 19-21]. The effect is unrelated to antihistaminergic activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The effect is unrelated to antihistaminergic activity [11]. Instead, Terfenadine is in part effective by mitochondrial depolarization [16], cytochrome c release [16], oxidative stess [12], increase of cytotosolic Ca 2+ activity ([Ca 2+ ] i ) [11] and activation of caspases [12,15,16].…”
Section: Introductionmentioning
confidence: 99%